Teologi Poros Tengah: Satu Kajian terhadap Afal al-Ibad dalam Pemikiran Kalam al-Asyari - Sobur, H.A. Kadir (Media Akademika, 2002)
This study attempts to elaborate humans activities (afal al-ibad) in the perspective of theology of middle way. It specially discusses Asarite point of view in that matter. The writer tries to relate Asyaris background of life to the event of his conversion into middle way and left his teachers circle (then school). The writer finally comes to a conclusion that it is by this method this school of theology succeeded in saving Islam from Hellenism.